The European Union as a security actor: Perspectives from the maritime domain - Jessica Larsen (Danish Institute for International Studies (DIIS), 2019)
The report analyses the EU's maritime security operations so far undertaken under the CSDP, the counter-piracy operation ATALANTA in the Indian Ocean and the counter-smuggling operation SOPHIA in the Mediterranean Sea.
Keywords: 300; Internationale Sicherheit; EU-Politik; Seeverkehrssicherheit; EU-Staaten